Counting Efficiencies Determined by Monte Carlo Methods for In Vivo Measurement of 131I Activity in Thyroid. Issue 4 (October 2019) - Park, MinSeok; Kwon, Tae-Eun; Ha, Wi-Ho; Kim, Chan Hyeong; Park, Sunhoo; Jin, Young Woo
Abstract : Abstract: The counting efficiencies obtained using a physical neck phantom are typically used in the measurement of 131 I activity in the thyroid. It is well known, however, that the geometrical discrepancies between the physical neck phantom and the anatomy of the subject can significantly influence the counting efficiencies. Thus, it is necessary to consider the anatomical characteristics of individuals if we need to accurately determine the activity of 131 I in the thyroid. This study aims to produce individualized counting efficiencies for thyroid measurement, considering the age, sex, and overlying tissue thickness of the subject being measured by Monte Carlo simulation. Simulations were performed using a series of computational human phantoms of different ages and sexes. The difference in counting efficiencies, depending on the age and sex of the phantom, were found to range from −26 to 3% for the phantoms and monitoring systems considered in the present study. The overlying tissue thickness of the computational phantoms was also modified to find the relationship between the counting ratio of the 80.2 and 364 keV gammas from 131 I and the overlying tissue thickness. The equations for estimating the overlying tissue thickness of a subject were then derived from the relationships between counting ratios and overlying tissue thickness. Finally, in the present study, a set of equations representing the variation in counting efficiencies for the 364 keV peak as a function of the overlying tissue thickness were derived, which can be used to determine individualized counting efficiencies for the subject being measured. These individualized counting efficiencies considering the overlying tissue thickness given a subject's age and sex can provide accurate estimates of 131 I activity for internal dosimetry.